How University Research can Create Impact - Haseeb, A.S.M.A (Journal of Research Management and Governance, 2020)
Universities are under increasing pressure to demonstrate that research carried out by using public money creates significant impact beyond academia which are categorized as cultural, economic, environmental, social, health and well-being, policy influence and change, legal and technological developments. Research impact is complex, diverse and long term in nature. The linear Results Chain Model suggests that a research project can go through a few phases before it creates impact: 1. Inputs, 2. Activities, 3. Outputs, 4. Outcomes, and 5. Impact. In this long process, researchers have a greater role to play in the early phases. In the later phases, researchers alone cannot make much progress without engaging with appropriate stakeholders. Stakeholders may include industry, policymakers, NGO, etc. depending on the type of the project. Researchers need to deliberately aim at non-academic impact, in addition to their traditional intellectual contributions. Universities, on their part, have to provide a supportive environment for researchers to pursue impact. The presence of effective ecosystems at national and regional levels is a necessary condition for increasing the chances of creating impact out of university research.